LO58: Using volunteers to improve the experience of older patients in the emergency department. (May 2020) - Ellis, B.; Melady, D.; Foster, N.; Sinha, S.; Lau, V.; Saraga, S.; McLeod, S.
Abstract : Introduction: The Maximizing Aging Using Volunteer Engagement in the ED (MAUVE + ED) program connects specially trained volunteers with older patients whose personal and social needs are not always met within the busy ED environment. The objective of this study was to describe the development and implementation of the MAUVE + ED program and the activities performed with older patients by its volunteers. Methods: The MAUVE + ED program was implemented in the ED (annual census 65, 000) of a large academic tertiary hospital in Toronto, Ontario. Volunteers were trained to identify and approach older patients and others at greater risk for adverse outcomes, including poor patient experience, in the ED and invite such patients to participate in the program. The program is available to all patients >65 years, and those with confusion, patients who were alone, those with mobility issues, and patients with increased length of stay in the ED. Volunteers documented their activities after each patient encounter using a standardized paper-based data collection form. Results: Over the program's initial 6-month period, the MAUVE + ED volunteers reported a total of 896 encounters with 718 unique patients. The median (IQR) time a MAUVE volunteer spent with a patient was 10 (5, 20) minutes, with a range of 1 to 130 minutes. The median (IQR) number of patients seen per shift was 7 (6, 9), with a range of 1 to 16 patients per shift. The most common activities the volunteer assisted with were therapeutic activities/social visits (n = 859; 95.9%), orientation activities (n = 501; 55.9%), and hydration assistance (n = 231; 25.8%). The least common were mobility assistance (n = 36; 4.0%), and vision/hearing assistance (n = 13; 1.5%). Conclusion: Preliminary data suggest the MAUVE + ED volunteers were able to enrich the experience of older adults and their families/carers in the ED.